Hardware based cryptography: technological advances for applications in Colombia using embedded systems - Gomez, Edwar Jacinto; Gutierrez, Caterinne Perilla; Murillo, Lina Uyasaba (Institute of Advanced Engineering and Science, 2021)
To have totally independent systems that offer a sufficient security scheme has become a necessity in Colombia, this because of the proliferation of IoT type systems and similar; In general, it is required to make stand-alone systems totally independent and distributed to offer users a solution to this need, this work offers the analysis and comparison of two security schemes type digital signature and/or hardware security module (HSM) and its variations, made on embedded platforms type microcontroller software, which shows the strategy to provide information protection, In addition, it is analyzed how each implementation was executed, in which devices and metrics of interest, in the first application the cryptography schemes were made using a deep programming that describes the algorithms in C++ language and in the second implementation the use of the dedicated hardware that the embedded platform type microcontroller had is detailed; In both cases, solutions with an acceptable throughput were generated, allowing to obtain comparable solutions and the same style as those made in a PC or similar hardware. On the other hand, an exhaustive review of this type of solutions in the country-region was made, in order to have a reference as to the possible use of this type of applications.